Glacial geomorphology of Marguerite Bay Palaeo-Ice stream, western Antarctic Peninsula. - Livingstone, S.J.; O'Cofaigh, C.; Stokes, C.R.; Hillenbrand, C-D.; Vieli, A.; Jamieson, S.S.R. (Journal of Maps, 2013)
This paper presents a glacial geomorphological map of over 17,000 landforms on the bed of a major palaeo-ice stream in Marguerite Bay, western Antarctic Peninsula. The map was compiled using various geophysical datasets from multiple marine research cruises. Eight glacial landform types are identified: mega-scale glacial lineations, crag-and-tails, whalebacks, gouged, grooved and streamlined bedrock, grounding-zone wedges, subglacial meltwater channels, gullies and channels, and iceberg scours. The map represents one of the most complete marine ice-stream signatures available for scrutiny, and these data hold much potential for reconstructing former ice sheet dynamics, testing numerical ice sheet models, and understanding the formation of subglacial bedforms beneath ice streams. In particular, they record a complex bedform signature of palaeo-ice stream flow and retreat since the last glacial maximum, characterised by considerable spatial variability and strongly influenced by the underlying geology. The map is presented at a scale of 1: 750,000, designed to be printed at A2 size, and encompasses an area of 128,420 km2.